Gestión de talento humano en la Corporación Nacional de Electricidad - CNEL EP Los Ríos, periodo 2023. - Dorotineo Santistevan, Joffre Daniel (2024)
The present case study was developed at the National Electricity Corporation CNEL EP Los Ríos. The context of the research was about human talent management, taking into account that it is a relevant aspect for all types of organizations to provide an adequate service and thus achieve the business goals that have been proposed. The objective of the research was to analyze the human talent management at the National Electricity Corporation CNEL EP Los Ríos during the year 2023, with the clear purpose of knowing how the different processes are executed, such as recruitment, selection, training and evaluation of personnel. The present work was based on a deductive method, which was descriptive and had a qualitative-quantitative approach. Among the results obtained, it was evident that the institution manages its personnel acceptably, however, negative aspects were found such as the limitation for all employees to access training programs. Aspects such as internal communication and the ability to establish personnel needs are highlighted, as well as the proper use of recruitment and selection processes, in order to have suitable personnel in the positions. For this research, the line of research of the Commerce Degree was considered: Management, finance, administration, tax, auditing and control; as well as the sub-line of research: Public and private companies and institutions.